Sex Radical Cinema - Siegel, Carol, 1952- (Book collections on Project MUSE., 2015)
In this provocative study of cinematic and televisual representations of "sex radicalism," Carol Siegel explores how representations of sexually explicit content on film have shaped American cultural visions of sex and sexual politics in the 21st century. Siegel distinguishes between a liberal approach to visual representations, which has over-emphasized normative equal opportunity while undervaluing our distinctive erotic selves, and a radical approach to visual representation, which portrays forbidden sexualities and desires. She illustrates how visual media participates in and even drives political policies related to pedophilia, prostitution, interracial relationships, and war. By examining such popular film and television shows as Mystic River, The Wire, Fifty Shades of Grey, Batman Returns, and the HBO hits, Sex and the City and Girls, Siegel takes the discussion of radical sex in the movies out of the margins of political discussions and puts it in the center, where, she argues, it has belonged all along.